Low-level laser treatment's ability to reduce dry socket pain - Giuseppe Minervini; Rocco Franco; Mirko Martelli; Salah Hafedh; Maria Maddalena Marrapodi; Marco Di Blasio; Patrizio Bollero; Marco Cicciù (Medical Journals Sweden, 2024)
After a tooth extraction, a dry socket is a common problem that can cause excruciating pain and prevent healing. Antiseptic dressings have historically been the mainstay of treatments for this illness in order to lower bacteria and accelerate healing. Alveogyl is a medicated dressing composed of butamben, iodoform, and eugenol is conventionally used to manage the pain associated with dry socket. The purpose of this study is to assess how well laser therapy treats alveolitis symptoms. The idea that laser therapy is an excellent tool for treating alveolitis is what motivated this meta-analysis. This systematic review aims to evaluate the effects of Level Laser Therapy (LLT) in the treatment of dry socket.  Methods: A literature search was done on PubMed, Lilacs, Web of Science, Scopus, and Cochrane using the keywords entered, and papers published between January 2000 and September 2023 were taken into consideration. The terms "laser" and "dry socket" have been merged using the Boolean conjunction AND; the results show that 65 studies could be identified using the three search engines. Only five were selected to create the current systematic study and metanalysis. The meta-analysis demonstrated that laser therapy is superior to the traditional Alvogyl treatment in managing alveolitis symptoms, especially in pain reduction. The overall effect demonstrated a mean difference of −2.01 (95% CI: −2.43 to −1.59) on the third day of treatment, with a p < 0.05, indicating statistical significance.  Conclusion: The quantitative analysis showed that Low-Level Laser Therapy demonstrated promising potential in managing alveolitis symptoms, particularly in terms of pain reduction, when compared to traditional treatments like Alvogyl. Despite the results indicating a statistically significant reduction in pain, the evidence does not conclusively establish laser therapy as a complete substitute for conventional therapies. Further high-quality studies with larger sample sizes and standardized protocols are required to confirm its long-term efficacy and to assess its broader applicability in clinical settings.